(untitled) (South East Asia Journal of Public Health, 2015)
Under the Revised National Tuberculosis Control Programme (RNTCP), Tuberculosis services are provided free of charge in India; all diagnosed TB patients are initiated on treatment within 7 days. Initial default is a potentially serious problem, particularly in cases of smear positive patients because they may continue transmitting the disease. This study was conducted to estimate the proportion of new sputum positive pulmonary TB patients who dropped out before initiating treatment, and their reasons for not registering for treatment. A cross-sectional study was carried out at Darjeeling District from July 2011 to April 2012 among 132 initial defaulters. Initial defaulter rate was 23.5%. A majority of the defaulters were 15-29 years old (59.10%); male (70.45%); from rural areas (80.06%); literate (78.79%); employed (86.36%); married (71.97%); non-smokers (77.27%); and had a mean per capita monthly income of Rs 741.40. Age, literacy, employment, marital status, smoking habits, alcohol consumption and pre treatment counseling were associated more among males than females and the differences were statistically significant. Among busy with other jobs, 76.19 % of patients were from a rural area, 71.43%were below the mean age, 73.81% had below mean per capita income. Among temporary vocational migration, 87.8% of patients were from rural areas, 56.1% were below the mean age, 63.41% had below mean per capita income. Among idle at home, 78.57% patients were from rural areas, 60.71% were below mean age, 75% had below mean per capita income. There is a need to convince the tuberculosis patients for initiating and completing treatment. DOI: http://dx.doi.org/10.3329/seajph.v4i1.21839 South East Asia Journal of Public Health Vol.4(1) 2014: 41-47